INFLUENCE OF BACTERIOCINS PRODUCED BY Lactobacillus plantarum LPBM10 ON SHELF LIFE OF CACHAMA HYBRID FILLETS Piaractus brachypomus x Colossoma macropomum VACUUM PACKAGED - SUÁREZ M., Héctor; de FRANCISCO, Alicia; BEIRÄO, Luiz H. (Vitae, 2009)
Some lactic acid bacteria genera (BAL) as Lactobacillus, Leuconostoc, Lactococcus or their antimicrobial products as bacteriocins are used as alternatives biopreservation of minimally processed foods kept under refrigeration. Potential Biopreservatives from a bacteriocin producer native strain, Lactobacillus plantarumLPBM10 ,was evaluated on fillets of cachama hybrid Piaractus brachypomus x Colossoma macropomum, vacuum-packed and stored at 30±0,5°C during 30 days. The evaluation was undertaken using three treatments, bacteriocins raw extract, lactic acid and control. There were not differences among treatments on Mesophylls count. Meanwhile, psychotrophylls count reached values for fillets treated with raw extract of bacteriocins, lactic acid and control, 5.2 cycles log, 6.7 cycles log and 6.4 cycles log (P<0.05), respectively. Regarding total coliforms, 2.6 cycles log of initial count was obtained, maintaining the same value until the end of storage. Faecal coliforms count, at the end of storage period diminished 1.3, 1.5 and 2.1 cycles log for fillets control treated with raw extract of bacateriocins and lactic acid, respectively. BVT-N analysis showed the best results on treatment with raw extract of bacteriocins and end with 19.3 mg BVT-N/100g. Sensorial analysis results showed the greater acceptability range for bacteriocins raw extract treatment.